The making of clinical psychology: Reisman J (1991) A history of clinical psychology. New York: Hemisphere (1971). - Edwards, David (PINS-Psychology in Society, 2026)
John Reisman’s A history of clinical psychology offers some informative lessons for clinical psychology in South Africa in this time of re-evaluation and reconstruction. This is the second edition of a book originally published 20 years ago, and it sets out to document the major developments in psychological concepts, assessment and therapy techniques and professional activity and structure as they have occurred chronologically. It is very much a North American book whose focus is on the development of clinical psychology in the U.S.A. but the many important theoretical developments that occurred in Europe are also thoroughly covered.